Peran Kejaksaan dalam Penyidikan Tindak Pidana Korupsi di Kejaksaan Negeri Denpasar - Ida Bagus Dwi Suryana Putra; Anak Agung Putu Wiwik Sugiantari (Jurnal Hukum Mahasiswa, 2026)
Corruption crimes which requires an active role of the Public Prosecutor’s Office not only as a public prosecutor but also as an investigator in law enforcement. The research problems addressed in this study are how the mechanism and procedures of corruption investigation are implemented at the Denpasar District Prosecutor’s Office and how the role of the Prosecutor’s Office is carried out in such investigations. This research uses empirical legal research with data collection techniques through direct interviews with prosecutors of the Special Crimes Division at the Denpasar District Prosecutor’s Office and supported by literature studies on relevant laws and legal references. The results of the research indicate that the mechanism and procedures for investigating corruption crimes at the Denpasar District Prosecutor’s Office have been implemented in accordance with criminal procedural law and internal guidelines of the Prosecutor’s Office, starting from the investigation stage, escalation of cases to formal investigation, examination of witnesses and suspects, until the case files are declared complete. Furthermore, the role of the Prosecutor’s Office in corruption investigation is strategic since it functions as the controller of the case from the early stage of investigation to prosecution, although in practice there are still technical constraints and inter-agency coordination issues that affect the effectiveness of the investigation process.